Education By Nurses To Reduce Anxiety For Families Of Patients Treated In The Covid-19 Isolation Room - Jumini Jumini; Hanna Hanidyastiti; Supriyadi Supriyadi; Ayu Budiati (Interest : Jurnal Ilmu Kesehatan, 2022)
Background: Anxiety disorders experienced by families with patients being treated in the COVID-19 isolation room are harmful to the mental and physical health of the family.  This study aims to determine the effect of education provided by nurses through digital media on reducing the anxiety level of the patient's family in the isolation room. Methods: True experiment study with the number of samples taken 36 people. The samples consist of 18 people in an experimental group who were given digital education and 18 people in a control group who were given face-to-face education. Data analysis using an independent t-test.  Results: There is a significant effect of providing education by nurses both through digital media and face-to-face in reducing the anxiety level of families of isolated inpatients at RSUP Surakarta (P value 0.000). Conclusion: Education through digital has proven to be more effective in reducing the anxiety of the patient's family in the isolation room of RSUP Surakarta compared to education through face-to-face.